Letter to Jane Tolmach from Paul Ziffren - Paul Ziffren:::::: (1976)
This letter, dated April 20, 1976, is from Paul Ziffren of the law firm Ziffren and Ziffren in Los Angeles to Jane Tolmach's Assembly campaign committee. Ziffren writes that he and Mickey were pleased to receive Jane's April 15 note and are enclosing a check to support her campaign. He extends their good wishes for her efforts. The letter is brief and cordial, indicating financial support for her candidacy. A handwritten note at the bottom adds personal regards.